Una probable divinidad tartésica identificada: NIETHOS/NETOS (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
An interesting graffiti, NIH80I, is written on bowl from  Miletos found in Huelva. It appeared in a archaeological ambience with East- Greek pottery dated between 590–560 B.C. probably related with a har- bour-sanctuary of the tartessian town of Onuba (Huelva).Niethos should be the first tartessian god-name known. It can be related with Neton, a warrior and solar divinity from Acci (Guadix, Gra- nada)  referred  by   Macrobius  (I,19,5).  Its   indoeuropean  root,  *nith-,*neith-, mains “warrior, hero”, “shining” and “holy”, and it is attested in Celtic and perhaps in the Celtiberian word neito and the Iberian neitin.These got-name Niethos-Neton should confirm  the existence  of Celts in Tartessos at the beginning of the VI century B.C. and would indicate its solar and warrior character, as a smiting god of the tartessian orientalizing culture, with functions of dynastic and town deity warran- tor of colonial exchanges.